Analysis Of Bioactive Compounds in Ethanolic Extract of Xylopia Aethiopica Leaves Using Gas Chromatography and Mass Spectrometry (GC-MS) Technique - Alagbe, J.O., Kadiri, Mercy. C.; Oluwafemi, R.A., Agubosi, O.C.P, Anorue, D. N. (European Science Publishing, 2023)
This study investigated the bioactive compounds in ethanolic extract of Xylopia aethiopica leaves using gas chromatography and mass spectrometry (GC-MS) technique. The phytoconstituents present in Xylopia aethiopica leaves were: flavonoids (951.82 mg/g), tannins (282.70 mg/g), alkaloids (188.47 mg/g), phenols (603.25 mg/g), saponins (11.47 mg/g), steroids (91.20 mg/g), oxalates (190.32 mg/g) and glycosides (190.32 mg/g). A total number of 30 bioactive compounds were identified based on their peak areas. The major compounds greater than 1 % were; 13-docosenamide (21.09 %), terpineol (10.07 %), 1,6-cyclodecadiene (9.37 %), copaene (2.88 %), caryophyllene (8.15 %), β-ocimene (6.05 %), β-myrcene (5.09 %), copaene (2.38 %), 2 – methoxy-4-vinylphenol (1.72 %), β-elemenone (1.31 %), 3,4-dimethylphenyl heptyl ether (1.26 %), ethyl oleate (1.07 %) and γ-elemene (1.27 %) while those less than 1 % (˂ 1 %) were; 2- methylenebornane (0.66 %), 2-methoxy-2-prophenyl (0.72 %), hexadec-7-enal (0.23 %), hexadecanoic acid (0.02 %), didodecyl benzene 1,2 dicarboxylate (0.09 %), methyl stearate (0.16 %), 9,12-octadecadienoic acid (0.08 %), hexadeca-7,10 – dienal (0.47 %), 1,1,5 –trimethyl -1,2-dihydronaphthalene (0.01 %), propane, 1,1 – oxybis -3- chloro (0.08 %), 1-trimethylsilypent-1-en-4-yne (0.03 %), bicyclo[13.1.0] hexade can-2-one (0.02 %), methyl octadeca-9-yn-11-trans-enoate (0.51 %), cis-linaloxide (0.22 %), tetradecanoic acid, 10,13 –dimethyl ester (0.18 %), didodecyl benzene 1,2 –dicarboxylate (0.47 %) and 2-cyclopentene -1-one, 2 – hyroxy (0.09 %). However, all the compounds have a wide range of pharmacological activities including- antimicrobial, antioxidant, anti-malarial, antifungal, anti-arrhythmic, anti-viral, hepato-protective, anti-proliferative, anti-depressant, antipyretic and antihelminthic.
Keywords: Xylopia aethiopica, anti-microbial, phytochemicals, gas chromatography, mass spectrometry, free radicals.